2012
DOI: 10.3390/ijerph9114197
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS and Associated Conditions among HIV-Infected Refugees in Minnesota, 2000–2007

Abstract: In 2010, the requirement for human immunodeficiency virus (HIV) testing of adult refugees prior to US resettlement was removed, thus leading to a potential for missed diagnosis. We reviewed refugee health assessment data and medical charts to evaluate the health status of HIV-infected refugees who arrived in Minnesota during 2000–2007, prior to this 2010 policy change. Among 19,292 resettled adults, 174 were HIV-infected; 169 (97%) were African (median age 26.4 (range: 17–76) years). Charts were abstracted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Among the 16 publications looking at physical health outcomes among all resettled refugee populations, 9 articles specific refugee adults as the target population [7,[11][12][13][14][15][16][17][18], and 7 articles specified refugee children [9,[19][20][21][22][23][24]. Most articles did not specify countries of origin, but rather grouped refugee country of origin into geographic regions (e.g., Southeast Asia and Africa).…”
Section: All Refugeesmentioning
confidence: 99%
“…Among the 16 publications looking at physical health outcomes among all resettled refugee populations, 9 articles specific refugee adults as the target population [7,[11][12][13][14][15][16][17][18], and 7 articles specified refugee children [9,[19][20][21][22][23][24]. Most articles did not specify countries of origin, but rather grouped refugee country of origin into geographic regions (e.g., Southeast Asia and Africa).…”
Section: All Refugeesmentioning
confidence: 99%
“…Ninety HIV-infected patients were recruited and tested for the presence of schistosomal and strongyloides antibodies. Mean [SD] age was 34 [ 6 ] years. Twenty six (29%) patients were male.…”
Section: Resultsmentioning
confidence: 99%
“…Limited data exists on the prevalence of helminth infections in HIV-infected immigrants. European have studies reported a prevalence of schistosomiasis ranging from 11% to 16% and prevalence of strongyloides ranging from 2% to 11% [ 3 - 5 ] in HIV infected immigrants while studies in the United States have reported a prevalence of between 3% and 29% for schistosomiasis and between 0.6% and 26% for strongyloides in HIV infected immigrants[ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antenatal HIV prevalence in this study (1.6%) is low compared to the prevalence rate found in asylum-seeking men and women in a small study in the UK (3.9%) and comparable to the prevalence rate observed in Italy (1.5%) [ 13 ]. The HIV prevalence among sub-Saharan African women who delivered in reception in our study (3.4%) was higher than among the sub-Saharan African asylum-seeking women who were tested for HIV at arrival in the United States (1.4%) [ 34 ]. The difference might be related to the composition of the study population (women who gave birth in The Netherlands compared to all women at arrival in the US) or to a different distribution of the countries of origin.…”
Section: Discussionmentioning
confidence: 99%